Histological analysis of nervous tissue of sprague dawley rats following sub-acute oral administration of Lignosus rhinocerotis (cooke) Ryvarden / Maseeha Farha - Maseeha , Farha (2019)
Lignosus rhinocerotis Cooke Ryvarden, known as Tiger Milk mushroom and locally knows as cendawan susu rimau is one of the medicinal mushroom widely used by the indigenous communities in Malaysia for various ailments. The sclerotium of the mushroom has been reported to possess anti-inflammatory, antioxidant, antimicrobial, anticancer and neuritogenic activities. This study aimed to examine if any, toxicity effect of L. rhinocerotis aqueous extract on nervous tissues of Sprague Dawley rats by subacute oral administration. Eighteen female rats were grouped into negative control that received 10 ml/kg body weight/day of distilled water, low dosage group and high dosage group that received 500 mg/kg body weight/day and 1000 mg/kg body weight/day of aqueous extract, respectively. Following the twenty-eight days oral administration, the rats were sacrificed, central and peripheral nervous tissues were harvested and processed for histological analysis. The gross examination of the nervous tissues of rats treated with L. rhinocerotis did not display any pathological changes compared to the negative control group. The microscopic features of peripheral nervous tissues namely, sciatic nerve and dorsal root ganglia and the central nervous tissues namely, cerebrum, cerebellum and spinal cord were normal. There were no abnormal clinical signs or body weight changes detected. Signs of toxicity such as neuronal degeneration and swelling or apoptosis of neurons, were not observed. No significant difference in distribution of cell bodies of sensory neurons, multipolar motor neurons, Betz cells and Purkinje cells between treated groups and negative control group were observed. In conclusion, the subacute oral administration of L. rhinocerotis aqueous extract had no adverse effects on nervous tissues.